Dispersal traits linked to range size through range location, not dispersal ability, in Western Australian angiosperms - Gove, Aaron; Fitzpatrick, M.; Majer, Jonathan; Dunn, Robert (Blackwell Science, 2009)
Aim:  We examine the relative importance of seed dispersal mode in determining the range size and range placement in 524 species from six focal plant families (Agavaceae, Euphorbiaceae, Malvacaeae, Sapindaceae, Proteaceae and Fabaceae (Acacia)). Location:  Western Australia. Methods  Taxa were categorized by dispersal mode and life-form and their distributions modelled using MAXENT. Geographical range size was compared amongst dispersal mode, life-form and biome using phylogenetically independent contrasts. Geographical range placement was considered in a similar manner. Results:  Range size did not vary with dispersal mode (ant versus wind and vertebrate dispersal) or life-form, and instead varied primarily as a function of the biogeographical region in which a species was found. Range placement, however, did vary among dispersal modes, with the consequence that diversity of wind- and ant-dispersed plants increased with latitude while the diversity of vertebrate-dispersed plants was more evenly distributed. Main conclusions:  For the taxa studied, range sizes were a function of the biogeographical region in which species were found. Although differences in range size may exist among species differing in dispersal modes, they are likely to be far smaller than differences among species from different biogeographical regions. The trait most likely to affect species geographical range size, and hence rarity and risks associated with other threats, may simply be the geographical region in which that species has evolved.